Encyclopedia of public international law in Asia - Yi, Sŏg-u, 1967-; Lee, Hee Eun (Leiden ; Boston : Koninklijke Brill NV, The Netherlands, 2021)
"The Encyclopedia is also available in print . Although there is general acknowledgement of the great variety of cultures among Asian countries, strong themes of familiarity, mutual understanding, coherence and solidarity persists among them as a result of the numerous mutual cultural and religious contacts and interconnections that developed over the course of centuries. The examination of international law and its application in Asia can reveal the shared history of the continent, but also its unique development in each Asian state: Incorporating the work of numerous leading scholars, the Encyclopedia of Public International Law in Asia provides a detailed description of the practice and implementation of international law in various Asian states. The Encyclopedia covers the introduction of Western international law; the resulting shift from Asian international law and the development of international law; and the impact that all of this has had on Asian states. Offered online and as a three-volume print set - Northeast Asia, Central and South Asia and Southeast Asia - this reference work is a valuable resource for all those interested in the historical development, implementation, and application of international law in Asia. Each jurisdiction included in the Encyclopedia follows a standard structure for the broadest comparative advantage: - Country Snapshot: Date of Independence, Date of Admission to the United Nations, Geographical Size, Population, Demographic Information, Form of Government, System of Law - State Report Overview: Executive summary of state report, Key highlights of unique state practice - Headings: THE STATE IN INTERNATIONAL LAW History and Theoretical Approach of [The State] in International Law Statehood & Sovereignty Territory & Jurisdiction Sovereign/State Immunity State Responsibility Relationship between International & Domestic Law INSTITUTIONAL RELATIONS Treaties Diplomatic & Consular Relations International & Regional Organisations Individuals & Non-State Actors International Relations & Cooperation Settlement of Disputes PARTICULAR INTERNATIONAL LAW SUBJECTS International Economic Law International Environmental Law Law of the Sea Air Law & Law of Outer Space Human Rights International Humanitarian Law International Criminal Law Use or Threat of Force"--
v. 1. Northeast Asia -- v. 2. Southeast Asia -- v. 3. Central & South Asia.
Keywords: International law -- Asia -- Encyclopedias